The dual role of autophagy in suppressing and promoting hepatocellular carcinoma - Mohammed, Wasnaa H.; Sulaiman, Ghassan M.; Abomughaid, Mosleh M.; Klionsky, Daniel J.; Abu-Alghayth, Mohammed H. (Frontiers in Cell and Developmental Biology, 2024)
The 5-year survival rate for hepatocellular carcinoma (HCC), a deadly form of liver cancer, is quite low. Although drug therapy is successful, patients with advanced liver cancer frequently develop resistance because of the significant phenotypic and genetic heterogeneity of these cells.The overexpression of drug efflux transporters, downstream adaptive responses, malfunctioning DNA damage repair, epigenetic modification, the tumor microenvironment, and the extracellular matrix can all be linked to drug resistance. The evolutionary process of autophagy, which is in charge of intracellular breakdown, is intimately linked to medication resistance in HCC.Autophagy is involved in both the promotion and suppression of cancer by influencing treatment resistance, metastasis, carcinogenesis, and the viability of stem cells. Certain autophagy regulators are employed in anticancer treatment; however, because of the dual functions of autophagy, their use is restricted, and therapeutic failure is increased. By focusing on autophagy, it is possible to reduce HCC expansion and metastasis, and enhance tumor cell reactivity to treatment. Macroautophagy, the best-characterized type of autophagy, involves the formation of a sequestering compartment termed a phagophore, which surrounds and encloses aberrant or superfluous components. The phagophore matures into a double-membrane autophagosome that delivers the cargo to the lysosome; lysosomes and autophagosomes fuse to degrade and recycle the cargo. Macroautophagy plays dual functions in both promoting and suppressing cancer in a variety of cancer types.